2023
DOI: 10.1111/jpn.13848
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of neurotoxicity and cognitive impairment induced by zinc nanoparticles by oral administration of saffron extract

Abstract: The accumulation of relatively higher dose of zinc oxide nanoparticles in brain was reported to produce neurotoxicity. Indeed, nanoparticles have a high ability to penetrate biological membranes and be uptaken by cells, which may cause cell disorders and physiological dysfunctions. The aim of the current study was to evaluate, whether oral administration of saffron extract, in rats, can protect from neurotoxicity and behavioural disturbances induced by chronic administration of ZnO‐NPs. Daily oral administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 121 publications
1
0
0
Order By: Relevance
“…Particularly, in the pineal gland, affron ® supplementation downregulated the gene expression of Il-6, whereas, in the liver, the treated rats showed decreased mRNA levels of Il-1β and TNF-α. These results agree with other studies that have found decreased gene expression of proinflammatory markers after treatment with a saffron extract in several tissues, such as in the cerebral cortex [62], the hippocampus [63], the aorta [2,64], the retina [65], the kidney [66], the pancreas [67], and the liver [68,69]. However, to our knowledge, this is the first study to report an anti-inflammatory effect after saffron supplementation in the pineal gland.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, in the pineal gland, affron ® supplementation downregulated the gene expression of Il-6, whereas, in the liver, the treated rats showed decreased mRNA levels of Il-1β and TNF-α. These results agree with other studies that have found decreased gene expression of proinflammatory markers after treatment with a saffron extract in several tissues, such as in the cerebral cortex [62], the hippocampus [63], the aorta [2,64], the retina [65], the kidney [66], the pancreas [67], and the liver [68,69]. However, to our knowledge, this is the first study to report an anti-inflammatory effect after saffron supplementation in the pineal gland.…”
Section: Discussionsupporting
confidence: 92%